South American H4N2 influenza A virus improved replication in chicken trachea after low number of passages - Ferreri, Lucas M.; Carnaccini, Silvia; Olivera, Valeria; Pereda, Ariel; Rajao, Daniela; Perez, Daniel R. (Frontiers in Veterinary Science, 2023)
Introduction of influenza A viruses (FLUAV) into poultry from wild aquatic birds is frequent, producing economic burden and increasing the probability of human infections. We have previously described the presence of FLUAV in wild birds in Argentina with unique evolutionary trajectories belonging to a South American lineage different from the North American and Eurasian lineages. Adaptability of this South American lineage FLUAV to poultry species is still poorly understood. In the present report, we evaluated the capacity of an H4N2 FLUAV from the South American lineage to adapt to chickens after low number of passages. We found that five mutations were acquired after five passages in 3-days-old chickens. These mutations produced a virus with better infectivity in ex vivo trachea explants but overall lower infection in lung explants. Infection of 3-week-old chickens persisted for a longer period and was detected in more tissues than the parental virus, suggesting adaptation of the H4N2 influenza A virus to chicken.